2018
DOI: 10.1002/2211-5463.12483
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of key genes, microRNAs and long non‐coding RNAs in hepatocellular carcinoma

Abstract: Human hepatocellular carcinoma (HCC) is a common aggressive cancer whose molecular mechanism remains elusive. We aimed to identify the key genes, microRNAs (miRNAs) and long non‐coding RNAs (lncRNAs) involved with HCC. We obtained mRNA, miRNA and lncRNA profiles for HCC from The Cancer Genome Atlas and then identified differentially expressed mRNAs (DEmRNAs), miRNAs (DEmiRNAs) and lncRNAs (DElncRNAs). We performed functional annotation of DEmRNAs and then constructed HCC‐specific DEmiRNA–DEmRNA, DEmiRNA–DElncR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Recent studies displayed that RCAN1 hinders the proliferation and angiogenesis of endothelial cells [7], which regulates the malignant progression of most human cancers. A large dozens of excellent reviews describe that RCAN1 significantly hampers cell proliferation, migration, and invasion of liver cancer [8][9][10]. However, the regulatory mechanism targeting this gene is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies displayed that RCAN1 hinders the proliferation and angiogenesis of endothelial cells [7], which regulates the malignant progression of most human cancers. A large dozens of excellent reviews describe that RCAN1 significantly hampers cell proliferation, migration, and invasion of liver cancer [8][9][10]. However, the regulatory mechanism targeting this gene is rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA, miRNA, pseudogene and circRNA are primarily involved in post-transcriptional regulation [ 7 ]. Recently, accumulating evidence has demonstrated that these ncRNAs are potential diagnostic and prognostic biomarkers for HCC [ 8 10 ]. Nevertheless, the specific functions and mechanisms of most ncRNAs in HCC remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Liver cancer is the second leading cause of cancer-related deaths worldwide,14 and HCC accounts for approximately 90% of all cases of primary liver cancer 15. Increasing evidence suggested noncoding RNAs, including lncRNAs and miRNAs, as important regulator in the development of HCC with potential diagnostic and therapeutic values 16. MALAT1 has been reported to exert oncogenic roles in multiple cancers, including HCC 1718.…”
Section: Discussionmentioning
confidence: 99%